2013
DOI: 10.1055/s-0032-1325932
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive diagnostic ability of endocytoscopy compared with biopsy for colorectal neoplasms: a prospective randomized noninferiority trial

Abstract: Endocytoscopy is noninferior to standard biopsy for the discrimination of neoplastic lesions. With its advantage of providing an on-site diagnosis, endocytoscopy could provide a novel alternative to standard biopsy in routine colonoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(71 citation statements)
references
References 27 publications
1
70
0
Order By: Relevance
“…In the present study, no malignant changes were detected; nonetheless, EC is able to detect malignant changes as it enables the assessment of nuclei in real time. A number of studies have reported the usefulness of EC in the diagnosis of epithelial neoplastic lesions (14,18,19). The current study supports previously reported endoscopic findings (6).…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, no malignant changes were detected; nonetheless, EC is able to detect malignant changes as it enables the assessment of nuclei in real time. A number of studies have reported the usefulness of EC in the diagnosis of epithelial neoplastic lesions (14,18,19). The current study supports previously reported endoscopic findings (6).…”
Section: Discussionsupporting
confidence: 91%
“…These have been proven to have excellent diagnostic performance, most of them achieving accuracies of greater than 90%; however, such accuracy can only be achieved by expert endoscopists. [10][11][12][21][22][23] The same is true of EC, an emerging endoscopic technology that allows real-time cellular imaging of alimentary mucosa and provides very accurate predictions of pathology (eg, accuracies of 94.1% 17 and 96.5% 25 for neoplastic change). 14,17,[24][25][26] However, with this technology as well, such accuracy is achieved only by trained and experienced expert endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] In contrast to the other modalities, the ultramagnification capability (450Â or 380Â) of EC enables on-site observation of nuclei, thus providing precise diagnosis of lesion pathology that can be as accurate (94.1%) as a biopsy (96.0%) for differentiating neoplastic polyps. 17 On the other hand, fundamental knowledge of pathology and clinical training coupled with experience are required to achieve accurate diagnoses; thus, EC has diagnostic benefits only when performed by experienced endoscopists.…”
mentioning
confidence: 99%
“…The EC findings according to the EC classification (EC-C), which is based on the glandular structure and cellular atypia of the lesion, were recorded. [13][14][15][16] Before obtaining EC images, staining with 1% methylene blue and 0.05% crystal violet was performed, which provided morphological images of the shape of the nuclei and gland duct lumens in the epithelial superficial layer. EC provides images that are similar to micrographic images of fixed specimens stained with hematoxylin and eosin; cell nuclei are clearly stained with methylene blue and cytoplasm with crystal violet, making it easy to identify the lumens of the glands.…”
Section: Colonoscopic Procedures and Endoscopic Diagnosismentioning
confidence: 99%
“…Previously, we reported that EC exceeds the diagnostic ability of both PIT and NBI-ME. [13][14][15][16] During EC, the ultra-magnified microvessels of the lesion can be observed, and they have been used to evaluate the inflammation grade of ulcerative colitis, 17 but there is little literature describing ultra-magnified microvessels in conjunction with colorectal neoplasm diagnoses. This pilot study investigated the ultra-magnified microvessel findings of colorectal lesions and compared their diagnostic ability with that of other modalities (eg, NBI-ME, PIT, and EC).…”
mentioning
confidence: 99%